AgroShare: a system for sharing and trading agricultural resources - Silva, Francis Da; Júnior, Nilton Assis; Batista, Bruno Guazzelli (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2024: Anais do XX Simpósio Brasileiro de Sistemas de Informação, 2024)
Context: In Brazil, agricultural activity is a factor of extreme importance for the socio-economic scenario. Problem: In the context of Brazil, where wealth is concentrated among a minority, small and medium-scale producers encounter a multitude of challenges and constraints that impede both expansion and the adoption of digital technologies on rural properties. Within this scenario, the procurement of essential agricultural resources, such as machinery, skilled labor, and the implementation of modern methodologies and techniques for crops and livestock, faces neglect or rejection due to constrained financial means. Proposed Solution: The goal of this project is to propose a system, called AgroShare, for the sharing and trade of agricultural resources among rural producers. SI Theory: A solution to these challenges is to change the way of negotiating and sharing resources in the field, applying methodologies already used in other scenarios such as Uber and Airbnb. Method: Analyses of works available in the literature allowed the modeling and development of AgroShare using technologies such as React Native, JavaScript XML and Firebase. Summarization of Results: An application was modeled and developed considering studies available in the literature. Analyses with stakeholders and normal users showed the developed application supplies its proposal. Contributions and Impact in the SI Field: AgroShare seamlessly aligns with the present socioeconomic and technological landscape of the country, characterized by the growing prevalence of human-computer interaction across diverse social strata. Moreover, it fosters connections in the pursuit of digitizing agricultural practices, aligning with the principles outlined by Smart Farms within the realm of the Internet of Things (IoT).